The tragic paradoxical effect of telemedicine on healthcare disparities- a time for redemption: a narrative review - Motti Haimi (BMC Medical Informatics and Decision Making, 2023)
Abstract Background Telemedicine has become more convenient and advantageous due to the rapid development of the internet and telecommunications. A growing number of patients are turning to telemedicine for health consultations and health-related information. Telemedicine can increase access to medical care by removing geographical and other barriers. In most nations, the COVID-19 pandemic imposed social isolation. This has accelerated the transition to telemedicine, which has become the most commonly utilized method of outpatient care in many places. Telehealth can assist resolve gaps in access to healthcare services and health outcomes, in addition to its primary function of boosting accessibility to remote health services. However, as the benefits of telemedicine become more apparent, so do the limitations of serving vulnerable groups. Some populations may lack digital literacy or internet access. Homeless persons, the elderly, and people with inadequate language skills are also affected. In such circumstances, telemedicine has the potential to exacerbate health inequities. Aim and methods In this narrative review (using the PubMed and Google scholar database), the different benefits and drawbacks of telemedicine are discussed, both globally and in Israel, with particular focus paid to special populations and to the telehealth usage during the Covid-19 period. Findings The contradiction and paradox of using telemedicine to address health inequities yet sometimes making them worse is highlighted. The effectiveness of telemedicine in bridging access to healthcare inequities is explored along with a number of potential solutions. Conclusions Policy makers should identify barriers among special populations to using telemedicine. They should initiate interventions to overcome these barriers, while adapting them to the needs of these groups.